Publication rate and evidence‐based evaluation of abstracts presented at the veterinary endoscopy society annual meeting (2004‐2019). (5th January 2022) - Moy‐Trigilio, Karen E.; Buote, Nicole J.; Parry, Stephen
Abstract: Objective: To determine the rate of full‐length publication for the 2004‐2019 Veterinary Endoscopy Society (VES) annual meeting abstracts and to identify abstract and author characteristics as predictors of publication. Study design: Observational bibliographical study. Sample population: Three hundred and eighty‐nine abstracts. Methods: Abstracts from 2004‐2019 Veterinary Endoscopy Society (VES) proceedings and matching full‐length publications retrieved from bibliographic databases were systematically reviewed. Variables assessed included species, specimen type (cadaver, live animal, etc.), subdiscipline (orthopedics, internal medicine, etc.), institution, country of origin, study design, level of evidence (LoE), time to publication, number of authors, their credentials, and gender. Logistic regression, Fisher's exact tests and t ‐tests were used to assess the bivariate relationship between publication and characteristics of the authors and publications. Results: The overall publication rate for presented abstracts published as full‐length articles in peer‐reviewed journals was 26%. Median time from abstract presentation to full‐length article publication was 430 days. Factors associated with full‐length article publication were identified: affiliated institution ( P = .01), species studied ( P = .04), subdiscipline focus ( P = .01), level of evidence ( P = .01), number of authors ( P = .01), and first author's gender ( P = .03). Conclusion: Veterinary Endoscopy Society abstracts were commonly categorized into a lower LoE. Abstracts from academic institutions regarding canine patients and soft tissue surgery topics were more likely to be published. Abstracts citing female first authors or with more than 1 author had higher odds of publication. Clinical significance: Data reported provide authors with predictors for publication and identify topics for research opportunities. Veterinary specialty societies may utilize this information when evaluating abstracts.